RESPONS TANAMAN KACANG HIJAU (Vigna radiata (L.) Wilczek) YANG DIBERI ANTIOKSIDAN DARI EKSTRAK KUNYIT TERHADAP CEKAMAN KEKERINGAN - Maman Suryaman; Yaya Sunarya; Ratna Beliandari (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2020)
Mungbean is one of important sources of vegetable protein in Indonesia. Extensification through the utilization of drylands is very potential to increase mungbean production. The study aimed to find out the response of mungbean given antioxidants of turmeric extract to drought stress. The study was conducted in Kuningan West Java in 2019. The study was designed using a randomized block design with factorial patterns and three replications. The first factor was the concentration of antioxidant of turmeric extract, namely: 0%, 1%, and 1.5%, and the second factor was soil water content namely: field capacity, 75% field capacity, and 50% field capacity. The results showed that the yield of seeds remained high even though mungbean experienced mild stress (75% field capacity) by administering antioxidant of turmeric extract as much as 1% or 1.5%. Likewise, the number of seeds and relative water content of leaves remained high with the same treatment. Meanwhile, plant height, leaf area, and number of pods were increasingly reduced by decreasing the level of soil water content, on the other hand, antioxidants increased the number of filled pods.